Philosophie der Verführung in der Prosa der Moderne : Polnische und deutschsprachige Autoren im Vergleich. - Hudzik, Agnieszka Helena (WeltLiteraturen / World Literatures., 2017)
A contribution to the philosophy and anthropology of literature, this book investigates seduction as an interpretative tool of modern fiction. The main axis of the study consists of comparative analyses of works by Robert Musil, Bruno Schulz, and Witold Gombrowicz. These authors use seduction in literary and theoretical texts to express their notions of art, subject, and reality.